The Effect of Normobaric Hypoxic Confinement on Metabolism, Gut Hormones, and Body Composition - Mekjavic, Igor B. (Front Physiol, 2016)
To assess the effect of normobaric hypoxia on metabolism, gut hormones, and body composition, 11 normal weight, aerobically trained (O(2peak): 60.6 ± 9.5 ml·kg(−1)·min(−1)) men (73.0 ± 7.7 kg; 23.7 ± 4.0 years, BMI 22.2 ± 2.4 kg·m(−2)) were confined to a normobaric (altitude ≃ 940 m) normoxic (NORMOXIA; P(I)O(2) ≃ 133.2 mmHg) or normobaric hypoxic (HYPOXIA; P(I)O was reduced from 105.6 to 97.7 mmHg over 10 days) environment for 10 days in a randomized cross-over design. The wash-out period between confinements was 3 weeks. During each 10-day period, subjects avoided strenuous physical activity and were under continuous nutritional control. Before, and at the end of each exposure, subjects completed a meal tolerance test (MTT), during which blood glucose, insulin, GLP-1, ghrelin, peptide-YY, adrenaline, noradrenaline, leptin, and gastro-intestinal blood flow and appetite sensations were measured. There was no significant change in body weight in either of the confinements (NORMOXIA: −0.7 ± 0.2 kg; HYPOXIA: −0.9 ± 0.2 kg), but a significant increase in fat mass in NORMOXIA (0.23 ± 0.45 kg), but not in HYPOXIA (0.08 ± 0.08 kg). HYPOXIA confinement increased fasting noradrenaline and decreased energy intake, the latter most likely associated with increased fasting leptin. The majority of all other measured variables/responses were similar in NORMOXIA and HYPOXIA. To conclude, normobaric hypoxic confinement without exercise training results in negative energy balance due to primarily reduced energy intake.